Factors influencing non-Muslim consumer’s awareness towards Halal logo on food product / Nur Shahira Joharin and Haiqal Syukri Jantan - Joharin, Nur Shahira; Jantan, Haiqal Syukri (Faculty of Business and Management, 2014)
Consumer awareness is the understanding by an individual of their rights as a consumer concerning available products and services being marketed and sold. The concept involves four (4) categories including safety, choice, information and the right to be heard. The diverse of Halal product in market has evidently rise Halal industry and this product is slowly being accepted around the world even towards non-Muslims. Now days Halal product is easily getting ease enter into any market is not only due to the rise of Muslims society but also with perception and awareness of community with all the benefit that they may gain. This matter has been expanding throughout the world and indirectly has attracted the attention of non-Muslims towards this kind of product. On this study, researchers determine the relationship between advertisements, safety food and health with non-Muslim consumer’s awareness towards Halal logo on food product. Researcher distributed 125 questionnaires to the respondents and used convenience sampling. Finding show advertisement, food safety and health has significance relationship with non-Muslim consumer’s awareness towards halal logo on food product. Overall, researcher managed to answer the objective.